Exploring Attachment Profiles in Emerging Adults: Insights from Global and Romantic Domains - Fernandez-Tapia, A (SAGE PUBLICATIONS LTD, 2025)
Despite previous studies documenting the existence of distinct attachment models that provide complementary information, there is a gap in research examining empirically attachment profiles that integrate both global attachment and attachment in specific domains from a person-centered approach. Based in the hierarchical structure of attachment representations, the present study evaluated the existence of different attachment profiles, using continuous scores of attachment anxiety and avoidance, in both global and romantic domains among 1,925 Chilean emerging adults. Additionally, and to assess the validity of these profiles, we investigated their association with mental health symptoms and relationship satisfaction. Through latent profile analysis (LPA), we identified five attachment profiles: and overall secure profile marked by security across both domains, one by insecurity across both domains (overall insecure), two profiles with elevated attachment anxiety (particularly in romantic domain) combined with moderate global avoidance, and a profile marked by high global attachment avoidance, and moderate romantic avoidance. The identified profiles were meaningfully associated with mental health symptoms and relationship satisfaction, supporting their validity. These results underscore the heterogeneity of internal working models in emerging adults, demonstrating that domain-specific divergence is common. They also highlight the added value of examining both global and romantic attachment to more fully capture the diversity of attachment experiences and relational functioning in this population.A pesar de que estudios previos han documentado la existencia de distintos modelos de apego que ofrecen informaci & oacute;n complementaria, existe una brecha en la investigaci & oacute;n que examine emp & iacute;ricamente perfiles de apego que integren tanto el apego global como el apego en dominios espec & iacute;ficos desde un enfoque centrado en la persona. Bas & aacute;ndose en la estructura jer & aacute;rquica de las representaciones de apego, el presente estudio evalu & oacute; la existencia de diferentes perfiles de apego, utilizando puntuaciones continuas de ansiedad y evitaci & oacute;n en el apego, tanto en los dominios global como rom & aacute;ntico, en una muestra de 1.925 adultos emergentes chilenos. Adem & aacute;s, y con el fin de evaluar la validez de estos perfiles, investigamos su asociaci & oacute;n con s & iacute;ntomas de salud mental y satisfacci & oacute;n en la relaci & oacute;n de pareja. A trav & eacute;s de un an & aacute;lisis de perfiles latentes (LPA, por sus siglas en ingl & eacute;s), identificamos cinco perfiles de apego: un perfil globalmente seguro caracterizado por seguridad en ambos dominios; uno por inseguridad en ambos dominios (globalmente inseguro); dos perfiles con ansiedad elevada en el apego (particularmente en el dominio rom & aacute;ntico) combinada con evitaci & oacute;n global moderada; y un perfil caracterizado por alta evitaci & oacute;n global en el apego y evitaci & oacute;n rom & aacute;ntica moderada. Los perfiles identificados se asociaron de manera significativa con s & iacute;ntomas de salud mental y satisfacci & oacute;n en la relaci & oacute;n, respaldando su validez. Estos resultados subrayan la heterogeneidad de los modelos operativos internos en adultos emergentes, demostrando que la divergencia espec & iacute;fica por dominio es com & uacute;n. Asimismo, destacan el valor a & ntilde;adido de examinar tanto el apego global como el rom & aacute;ntico para captar m & aacute;s plenamente la diversidad de experiencias de apego y el funcionamiento relacional en esta poblaci & oacute;n.